American women artists, past and present: a selected bibliographic guide - Tufts, Eleanor (Garland Pub, 1984)
Keywords: amériques; arts; bibliographie; cours; discipline; femmes* artistes; har4600; histoire de l'art; histoire et politique; pol4022; premier cycle; régions géographiques; thématiques; états-unis

Our hidden heritage: five centuries of women artists - Tufts, Eleanor (Paddington Press, 1974)
Our hidden heritage: five centuries of women artists unearths an unheralded legacy of art treasures by women artists. THrough individual biographies, the lives and work of twenty-two women artists are authoritatively described by Eleanor Tufts. These exciting portrayals provide new insights into the lives and works, the frustrations and successes of these talented women, as well as into their relationships with their contemporaries, husbands, freinds and families. Over 125 full-page reproductions of their works from major collections throughout the world demonstrate the variety and enduring quality of their art. Their lives and their work were as diverse as their cultures and their times.
Keywords: 1500-1599; 1600-1699; 1700-1799; 1800-1899; 1900-1999; arts; cours; discipline; femmes* artistes; har4600; histoire de l'art; histoire et politique; premier cycle; périodes historiques; thématiques